Weaving a Modern Plan for Canada's Capital: Jacques Gréber and the 1950 Plan for the National Capital Region - Gordon, David (Urban History Review / Revue d'histoire urbaine, 2001)
The 1950 Plan for the National Capital is one of the most significant documents in Canadian planning history. The plan was the guide for the rapid transformation of Ottawa and Hull from rather dreary industrial towns into an attractive modern capital. Jacques Gréber, a French architect, planner and landscape architect, headed the planning team. He was personally recruited by Prime Minister Mackenzie King to realize his dream of a capital that inspired pride among Canadians. Gréber was considered France's leading planner in mid-century, having completed plans for the Fairmount Parkway in Philadelphia, Lille, Marseilles and Rouen. Ironically, Gréber is almost forgotten in his native land, while his legacy is fondly remembered in North America.